Interstellar condensed (icy) amino acids and precursors: theoretical absorption and circular dichroism under UV and soft X-ray irradiation. Issue 1 (11th March 2014) - Da Pieve, F.; Avendaño-Franco, G.; De Proft, F.; Geerlings, P.
Abstract: The photophysics of interstellar ices and condensed molecules adsorbed on grains is of primary importance for studies on the origin of the specific handedness of complex organic molecules delivered to the early Earth and of the homochirality of the building blocks of life. Here, we present quantum mechanical calculations based on time-dependent density functional theory for the absorption and circular dichroism (CD) of isovaline and its chiral precursor 5-ethyl-5-methylhydantoin, both observed in meteoritic findings. The systems are considered in their geometrical conformation as extracted from a full solid (icy) matrix, as a shortcut to understand the behaviour of molecules with fixed orientation, and/or taking into account the full solid matrix. In the context of a possible 'condensation–warming plus hydrolysis–recondensation' process, we obtain that: (i) for low-energy excitations, the 'condensed' precursor has a stronger CD with respect to the amino acid, suggesting that the handedness of the latter could be biased by asymmetric photolysis of the precursor in cold environments; (ii) enantiomeric excess could in principle be induced more efficiently in both systems for excitation at higher energies (VUV). X-ray absorption near-edge spectroscopy and related CD results could serve as support for future experiments on ionization channels.